Alternative Measures of Credit Extension for Countercyclical Buffer Decisions in South Africa - RAPUTSOANE, Leroi (Journal of Advanced Studies in Finance, 2017)
This paper analyses the behaviour of alternative measures of credit extension for countercyclical buffer decisions in South Africa. These measures are the deviation of the ratio of private sector credit extension to gross domestic product from its long term trend, the deviation of the logarithm of private sector credit extension from its long term trend as well as the annual percentage change in private sector credit extension. The results show that the deviation of the ratio of private sector credit extension to gross domestic product from its long term trend is countercyclical with the economic cycle. The results further show that deviation of the logarithm of private sector credit extension from its long term trend is procyclical with both the economic and the financial cycle. The results finally show that annual percentage change in private sector credit extension generally performs poorly in cyclical terms with both the economic and the financial cycle. Consequently the deviation of the logarithm of private sector credit extension from its long term trend could be used as a common reference guide for implementing the countercyclical capital buffers in South Africa.